Deposition of beta/A4 immunoreactivity and neuronal pathology in transgenic mice expressing the carboxyl-terminal fragment of the Alzheimer amyloid precursor in the brain. - Kammesheidt, A (1992)
The deposition of amyloid in senile plaques and along the walls of the cerebral vasculature is a characteristic feature of Alzheimer disease. The peptide comprising the carboxyl-terminal 100 amino acids of the beta-amyloid precursor protein (beta APP) has been shown to aggregate into amyloid-like fibrils in vitro and to be neurotoxic, suggesting that this fragment may play a role in the etiology of Alzheimer disease. To address this question, we expressed this carboxyl-terminal 100-amino acid peptide of beta APP in transgenic mice under the control of the brain dystrophin promoter. We used an antibody to the principal component of amyloid, beta/A4, to demonstrate cell-body and neuropil accumulation of beta/A4 immunoreactivity in the brains of 4- and 6-month-old transgenic mice. Only light cytoplasmic staining with this antibody was visible in control mice. In addition, immunocytochemical analysis of the brains with an antibody to the carboxyl terminus of beta APP revealed abnormal aggregation of this epitope of beta APP within vesicular structures in the cytoplasm and in abnormal-appearing neurites in the CA2/3 region of the hippocampus in transgenic mice, similar to its aggregation in the cells of Alzheimer disease brains. Thioflavin S histochemistry suggested accumulations of amyloid in the cerebrovasculature of transgenic mice with the highest expression of the beta APP-C100 transgene. These observations suggest that expression of abnormal carboxyl-terminal subfragments of beta APP in vivo may cause amyloidogenesis and specific neuropathology.